Challenges and Progress of Orphan Drug Development for Rare Diseases - Debnath, Abhijit; Mazumder, Rupa; Mazumder, Avijit; Tyagi, Pankaj Kumar; Singh, Rajesh Kumar (Current Pharmaceutical Biotechnology, 2025)
Rare diseases, defined as conditions affecting fewer than 200,000 people in the United States or less than 1 in 2,000 people in Europe, pose significant challenges for healthcare systems and pharmaceutical research. This comprehensive review examines the evolving landscape of orphan drug development, analyzing scientific, economic, and regulatory challenges while highlighting recent technological breakthroughs and innovative approaches. We explore how artificial intelligence, next-generation sequencing, and personalized medicine are revolutionizing rare disease research and treatment development. The review details key advances in therapeutic approaches, including gene therapy, cell-based treatments, and drug repurposing strategies, which have led to breakthrough treatments for previously untreatable conditions. We analyze the impact of international collaborations, such as the International Rare Diseases Research Consortium, and discuss how regulatory frameworks worldwide have evolved to accelerate orphan drug development. The paper highlights the growing market for orphan drugs, projected to reach 242 billion by 2024 while examining the complex challenges of ensuring treatment accessibility and economic sustainability. We assess innovative clinical trial designs, patient registry development, and emerging strategies in personalized medicine that are transforming the field. Despite notable advancements, significant gaps remain in diagnosis, treatment accessibility, and sustainable funding for rare disease research. The review concludes by proposing specific actions for enhancing international collaboration, improving patient registries, and aligning incentives to address the unmet medical needs of rare disease patients, emphasizing the critical role of continued public-private partnerships and technological innovation in advancing orphan drug development.
Keywords: Orphan Drug Act